2008
DOI: 10.1103/physrevb.78.233407
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the electronic structure of graphene by ion irradiation

Abstract: Mechanically exfoliated graphene layers deposited on SiO2 substrate were irradiated with Ar+ ions in order to experimentally study the effect of atomic scale defects and disorder on the low-energy electronic structure of graphene. The irradiated samples were investigated by scanning tunneling microscopy and spectroscopy measurements, which reveal that defect sites, besides acting as scattering centers for electrons through local modification of the on-site potential, also induce disorder in the hopping amplitu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
185
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(191 citation statements)
references
References 30 publications
6
185
0
Order By: Relevance
“…Typically, irradiating graphene with energetic particles, such as ions [326,336338] or electrons [328,339], can effectively create point defects (mostly vacancies), due to the ballistic ejection of carbon atoms. Carbon atoms that gain sufficient energy (approximately 18–20 eV) from the irradiating beams may be sputtered away from graphene, get adsorbed on the sheet or migrate on the surface as adatoms.…”
Section: Modulation Of Structural Defects In Graphenementioning
confidence: 99%
“…Typically, irradiating graphene with energetic particles, such as ions [326,336338] or electrons [328,339], can effectively create point defects (mostly vacancies), due to the ballistic ejection of carbon atoms. Carbon atoms that gain sufficient energy (approximately 18–20 eV) from the irradiating beams may be sputtered away from graphene, get adsorbed on the sheet or migrate on the surface as adatoms.…”
Section: Modulation Of Structural Defects In Graphenementioning
confidence: 99%
“…In previous studies graphene has been irradiated with either low energy ions (LEI) or light ions and with high ion fluences of (from 10 11 ions/cm 2 up to 10 18 ions/cm 2 ) normal to the surface. These reports have shown that it is indeed possible to induce defects with energetic ions even in suspended graphene sheets [10,11,12,13]. Furthermore, it has been shown that by irradiating single layer graphene (SLG) with swift heavy ions (SHI) with ∼100 MeV kinetic energy under glancing incidence angle, origami like foldings of the graphene sheet are induced by individual ions [14].…”
Section: Introductionmentioning
confidence: 99%
“…Ion irradiation can be used to introduce structural defects in graphene and other carbon allotropes 16 , and provides a versatile tool for manipulating their physical properties 7,[17][18][19][20][21][22] For this purpose, proton irradiation, in particular, attracts much interest due to the observed irradiation-induced magnetism in graphite and graphene [23][24][25][26][27][28][29] , which was attributed to defects, e.g., vacancies and H species 24 . However, an atomic-resolved determination, e.g.…”
mentioning
confidence: 99%